DETERMINING THE ELEMENTS OF THE TEXT ON IMAGE USING OF FUZZY COGNITIVE MODELS - Pyatikop, Elena (International Journal of Computing, 2014)
This publication describes the modeling results of knowledge of cognitive psychology about the primary processing in the visual system to analyze the images in purpose to determine the elements of the text. Processing images at the level of primary visual cortex formalized using fuzzy sets.